The Will to Learn : Cultivating Student Motivation Without Losing Your Own - Stuart, Dave, Jr., 1948- (Thousand Oaks : Corwin Press, 2023)
"This is a book about love. That is, the active, earnest, and intelligent pursuit of our neighbors' good. Teachers embody this kind of love; we seek and serve the wholeness of others. At the center of this love lies Dave Stuart Jr.'s philosophy that every teacher of every subject area in our schools has the potential to enrich students' lives long term through the power of student motivation. From art and physical education to science and social studies--schools can make good on their promise, and this book will show you how. Join Stuart in this personal journey by tackling student motivation through: the Five Key Beliefs of credibility, value, effort, efficacy, and belonging, Ten strategies for incorporating the Five Key Beliefs into everyday teaching, Tactics to overcome common struggles for each strategy, A companion website with additional resources, videos, and downloadables. Do the work. Do it with care. These inspirational guideposts will help us all build a world in which our schools can be both productive and humane."--
Includes bibliographical references and index.
Keywords: Motivation in education; Educational psychology